Novel SNPs of TNF-a and IL-6 that Regulate Serum Level in Obese Patients - Omear, Hadeel (Journal of Biomedicine and Biochemistry, 2023)
Background Obesity is an abnormal amount of fats in the body that can result from several factors majorly including environmental and genetic fac- tors. The worldwide prevalence of obesity has increased tremendously in the last three decades and is now considered a global epidemic. Despite the negative impacts of obesity on human health and its majorly associated risk factors such as heart disease, diabetes, and certain types of cancers, no effective strategies have been employed to bring down its rate which can reach an alarming level in the next few years.Objective Previously, various studies have reported the high serum concentrations of two cytokines tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6) in obese patients. These genes (TNF-α and IL-6) are released from the adipose tissues stimulated by obesity. Considering their pivotal association with obesity, this study has been designed to investigate the relationship between SNPs of TNF-α and IL-6 and their high serum lev- els in obesity.Results Here, we utilized R language to perform statistical analyses such as correlation, normality testing, ROC, and regression analysis on serum levels of TNF-α and IL-6 between obese and control groups. Furthermore, the frequencies of clinical data and Hardy-Weinberg Equilibrium tests for allele and the genotypes analysis of the cytokines were performed. Conclusion The results of this study indicate that serum levels of TNF-α and IL-6 were significantly correlated with obesity SNPs.